2024
DOI: 10.1109/ojvt.2023.3335180
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review on Limitations of Autonomous Driving and Its Impact on Accidents and Collisions

Amit Chougule,
Vinay Chamola,
Aishwarya Sam
et al.

Abstract: The emergence of autonomous driving represents a pivotal milestone in the evolution of the transportation system, integrating seamlessly into the daily lives of individuals due to its array of advantages over conventional vehicles. However, selfdriving cars pose numerous challenges contributing to accidents and injuries annually. This paper aims to comprehensively examine the limitations inherent in autonomous driving and their consequential impact on accidents and collisions. Using data from the DMV, NMVCCS, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 111 publications
0
2
0
Order By: Relevance
“…In 2017, there was another incident involving a Tesla Model S, which collided with an 80-year-old cyclist [7]. These accidents highlight the urgency to develop reliable solutions in AVs that can prevent such incidents and ensure the safety of all road users [8]. Furthermore, research has shown that these incidents have caused a negative public perception of the technology [9].…”
Section: Background and Motivationmentioning
confidence: 99%
“…In 2017, there was another incident involving a Tesla Model S, which collided with an 80-year-old cyclist [7]. These accidents highlight the urgency to develop reliable solutions in AVs that can prevent such incidents and ensure the safety of all road users [8]. Furthermore, research has shown that these incidents have caused a negative public perception of the technology [9].…”
Section: Background and Motivationmentioning
confidence: 99%
“…Thus, while some studies imply that drivers may prefer manual control regardless of the intention of AVs, inconsistencies in previous research, alongside a conflict between the public choice theory and self-preservation principle, suggest that in level-3 automated driving, some drivers may delay takeover to avoid the guilt and responsibility associated with potential accidents. However, several recent AV accidents have shown that when facing unexpected situations, AVs may not operate safely [ 22 , 23 ], and intentionally taking over late could increase the severity of accidents—even if they are impossible to avoid. To solve this problem, in the present study, we aim to investigate the factors influencing takeover decisions in critical situations to explore ways to prevent intentionally late takeovers.…”
Section: Introductionmentioning
confidence: 99%